The effects of a constant sprint-to-rest ratio and recovery mode on repeated sprint performance - Abt, G.; Siegler, J. C.; Akubat, I.; Castagna, C. (The Journal of Strength and Conditioning Research, 2011)
It is unclear if a constant sprint-to-rest ratio allows full performance recovery between repeated sprints over different distances. This is important for the development of sprint-training programs. Additionally, there is conflicting evidence on whether active recovery enhances sprint performance. Three repeated sprint protocols were used (22 × 15, 13 × 30, and 8 × 50 m), with each having an active and passive recovery. Each trial was conducted with an initial sprint-to-rest ratio of 1:10. Repeated sprints were analyzed by comparing the first sprint to the last sprint. For the 15-m trials, there were no significant main effects for recovery or time and no significant interaction. For the 30-m trials, there was no main effect for recovery, but a main effect for time (F[1,10] = 15.995, p = 0.003; mean difference = 0.20 seconds, 95% confidence interval [CI] = 0.09-0.31 seconds, d = 1.4 [large effect]). There was no interaction of recovery and time in the 30-m trials. For the 50-m trials, there was no main effect for recovery, but a main effect for time (F[1,10] = 34.225, p = 0.0002; mean difference = 0.39 seconds, 95% CI = 0.24-0.55 seconds, d = 1.3 [large effect]). There was no interaction of recovery and time in the 50-m trials. The results demonstrate that a 1:10 sprint-to-rest ratio allows full performance recovery between 15-m sprints, but not between sprints of 30 or 50 m, and that recovery mode did not influence repeated sprint performance.